Transition from argatroban to oral anticoagulation with phenprocoumon or acenocoumarol: effects on prothrombin time, activated partial thromboplastin time, and Ecarin Clotting Time - Harder, Sebastian; Graff, Jochen; Klinkhardt, Ute; von Hentig, Nils; Walenga, Jeanine M.; Watanabe, Hikari; Osakabe, Masanori; Breddin, Hans-Klaus (Thrombosis and Haemostasis, 2004)
Treatment with the direct thrombin inhibitor argatroban (ARG) is often followed by vitamin K-antagonist treatment (VKA). Phenprocoumon (PC) and acenocoumarol (AC) are frequently used in Europe. The standard monitoring test for VKA, prothrombin time (PT), is prolonged by direct thrombin inhibitors. Therefore the International Normalized Ratio (INR) obtained during combined treatment does not reflect the true effect of the VKA. A similar interference of the VKA on the activated partial thromboplastin time (aPTT), a monitoring assay for direct thrombin inhibitors, can occur. In 39 healthy volunteers the effect of ARG alone or combined with PC or AC on PT, INR, aPTT, and Ecarin Clotting Time (ECT) was investigated. 6 groups each of 6-8 volunteers received a 5-hour infusion of either 1.0, 2.0 or 3.0 µg/kg/min ARG (days 1, 3, 4 and 5) before initiation of either PC or AC (day 1) and during continued VKA dosing (target INR 2-3). A linear relationship (INR ARG+VKA = intercept + slope * INR VKA alone) was observed between the INR measured “on” and “off” ARG.The slope depended on the argatroban dose and on the International Sensitivity Index (ISI) of the PT reagent, the steepest slope (i.e., the largest difference between INR ARG+VKA and INR VKA alone) was seen with the highest ARG dose and the PT reagent with an ISI of 2.13.There was a close correlation between plasma levels of ARG and aPTT or ECT. Under VKA the ARG-aPTT relationship indicated an increased sensitivity of the aPTT to ARG, VKA treatment had no effect on the prolongation of the ECT induced by argatroban. In conclusion, ARG at doses up to 2 µg/kg/min can be discontinued at an INR of 4.0 on combined therapy with VKA, as this would correspond to an INR between 2.2 and 3.7 for the VKA. If it is necessary to monitor ARG in the critical transition period, the ECT which is not influenced by VKA can be used as an alternative to the aPTT.
Keywords: Argatroban; phenprocoumon; acenocoumarol; interaction